NLOS identification based on RSS and TOA measurement for indoor UWB localization - Wang, Jiaxin (Nanyang Technological University, 2020)
Ultra-Wideband (UWB) radio is a promising technology that is widely used for indoor localization. However, its positioning accuracy is deteriorated by None Line of Sight (NLOS) signal propagation, which induces a positive bias in range estimation. The ability to identify NLOS is important in a localization system. In this project the scientific details of NLOS identification techniques for indoor UWB localization will be introduced. Proposed techniques could include measuring both the Received Signal Strength (RSS) and Time of Arrival (TOA) of the detected power delay profile. Additionally, the mitigation of the NLOS identification technique will be tested through MATLAB simulations and measurements. This project is designed and tailored towards experimental research in data analysis, signal simulation and measurements of UWB signal propagations and ranging in indoor environments.